2005
DOI: 10.1038/sj.npp.1300869
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 5-HT on Memory and the Hippocampus: Model and Data

Abstract: 5-Hydroxytryptamine (5-HT) transmission has been implicated in memory and in depression. Both 5-HT depletion and specific 5-HT agonists lower memory performance, while depression is also associated with memory deficits. The precise neuropharmacology and neural mechanisms underlying these effects are unknown. We used neural network simulations to elucidate the neuropharmacology and network mechanisms underlying 5-HT effects on memory. The model predicts that these effects are largely dependent on transmission o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 56 publications
2
38
0
Order By: Relevance
“…Studies showing impaired recall and memory consolidation in volunteers following tryptophan depletion, [65][66][67] the therapeutic efficacy of selective serotonin reuptake inhibitors in BN, 68 and inconsistency regarding any benefit of fluoxetine in ''weight-recovered'' AN 69,70 suggest the possibility of serotonergic disturbance in BN being different to that in AN. Increased 5-HT 1A receptor functioning in the subgenual cingulate and mesial temporal regions of acutely ill and ''recovered'' BN as compared to AN patients, 27 and the amelioration of memory deficits by 5-HT 1A agonists, albeit in depressed populations, 71 also suggest differentially altered serotonergic systems in BN and AN. A limitation of the current study was that cortisol and prolactin responses to a serotonin agonist were not assessed, so as to gauge serotonin functioning and responsiveness in the different clinical population groups.…”
Section: Resultsmentioning
confidence: 97%
“…Studies showing impaired recall and memory consolidation in volunteers following tryptophan depletion, [65][66][67] the therapeutic efficacy of selective serotonin reuptake inhibitors in BN, 68 and inconsistency regarding any benefit of fluoxetine in ''weight-recovered'' AN 69,70 suggest the possibility of serotonergic disturbance in BN being different to that in AN. Increased 5-HT 1A receptor functioning in the subgenual cingulate and mesial temporal regions of acutely ill and ''recovered'' BN as compared to AN patients, 27 and the amelioration of memory deficits by 5-HT 1A agonists, albeit in depressed populations, 71 also suggest differentially altered serotonergic systems in BN and AN. A limitation of the current study was that cortisol and prolactin responses to a serotonin agonist were not assessed, so as to gauge serotonin functioning and responsiveness in the different clinical population groups.…”
Section: Resultsmentioning
confidence: 97%
“…As we found no differences, one could argue that the applied dosage was too low to influence response inhibition or re-engagement. It has been suggested that the association between serotonergic activity and cognition can be described in terms of an inverted U-curve (Meeter et al, 2006;Schmitt et al, 2006). That is, both under-stimulation as well as overstimulation of the serotonergic system resulting from either decreased or increased 5-HT levels may imbalance the cortical network e.g., responsible for memory function and lead to effects.…”
Section: Discussionmentioning
confidence: 99%
“…Methods were not available that would allow non-invasive assessment of central 5-HT transmission or determination of the specific neurochemical mechanisms underlying the increased neurophysiological responsiveness to emotional stimuli observed during tryptophan depletion in these regions. However, it has been argued (Meeter et al, 2006) that the net effect of tonic 5-HT transmission is to hyperpolarize glutamatergic neurons (at least in the hippocampus), primarily via the 5-HT 1A receptor, but also via 5-HT 3 and 5-HT 6 receptors. It is therefore conceivable that the cause of increased responsiveness of these subcortical structures to emotional stimuli following 5-HT depletion was a loss of inhibitory tone provided by these 5-HT receptor subtypes.…”
Section: Discussionmentioning
confidence: 99%